2020
DOI: 10.1021/acs.orglett.0c02641
|View full text |Cite
|
Sign up to set email alerts
|

Terreuspyridine: An Unexpected Pyridine-Fused Meroterpenoid Alkaloid with a Tetracyclic 6/6/6/6 Skeleton from Aspergillus terreus

Abstract: Terreuspyridine (1), the first 3,5-demethylorsellinic acid (DMOA) derived meroterpenoid alkaloid, was isolated from the fungus Aspergillus terreus, which represents a new type of meroterpenoid possessing an unexpected tetracyclic 6/6/6/6 architecture. The structure of 1 with absolute configuration was determined by X-ray diffraction analysis. Biogenetically, it was proposed to be derived from the fusion of a DMOA-meroterpenoid and a glutamate. Terreuspyridine (1) exhibited moderate inhibitory activity against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…The data summarized above indicate that 1 is a meroterpenoid pyridine alkaloid with a tricyclic ring system. 9,10…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data summarized above indicate that 1 is a meroterpenoid pyridine alkaloid with a tricyclic ring system. 9,10…”
Section: Resultsmentioning
confidence: 99%
“…Pyridines are privileged scaffolds in medicinal chemistry, 5 and the nitrogen atom in pyridine plays a crucial role in the pharmacological profiles of many drugs that contain this heterocycle. 6 Thus, pyridine alkaloids display rich structural diversity and widespread bioactivity, such as anti-allergic dysivillosins, 7 cardioprotective scrophularianines, 8 anti-butyrylcholinesterase terreuspyridine 9 and anti-acetylcholinesterase amphichoterpenoids, 10 which have attracted widespread attention from chemists and pharmacologists to further explore their structural diversity, biosynthesis and bioactivities. 11–15…”
Section: Introductionmentioning
confidence: 99%
“…Terreuspyridine displayed moderate inhibitory effects against butyrylcholinesterase (BChE) with an IC50 value of 16.4 μM. Further molecular docking revealed that terreuspyridine fit well in the binding pocket of BChE (Li et al 2020a).…”
Section: Terpenoid Alkaloidsmentioning
confidence: 99%
“…Aspergillus rugulosa , a strain producing aspertetronin A, 14 is known to produce polyketides, meroterpenoids and xanthone. 15–17 In our continuing efforts on natural bioactive metabolites from fungi using a large-scale cultured method, 18–23 the first furancarboxylic acid homologous dimer, asperosin A ( 1 ), featuring a unique hetero-bicyclic 6/5 core skeleton, which is constructed from four continuous quaternary carbons, along with two known biosynthetically related compounds ( 2 and 3 ), were isolated and characterized from the culture of Aspergillus rugulosa (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%